Degradation of Spark Plasma Sintered Yttria Stabilized Zirconia (YSZ) and CeO2‐YSZ Ceramics in Supercritical Water. Issue 6 (3rd November 2014) - Siebert‐Timmer, A.; Bichler, L.; Mondal, K.
Abstract : Zirconia ceramics are often considered in the nuclear industry for high temperature applications due to their radiation resistance, chemical inertness, high thermal stability and low thermal conductivity. However, wide application of zirconia ceramics is hindered by their degradation behavior in aqueous media. In this research, moderately dense 8 mol% Yttria Stabilized Zirconia (YSZ) as well as YSZ based ceramics containing 5, 10 and 15 mol% CeO2 were fabricated via Spark Plasma Sintering (SPS). Sintered ceramics were subjected to static degradation testing in supercritical water at 400°C and 31 MPa. The weight loss and microstructural changes of the ceramics associated with supercritical water exposure were studied, and the results suggest that the addition of CeO2 significantly reduced the degradation rate and improved the bulk structural stability of the ceramic composite. This behavior was attributed to the enhanced stabilization of the zirconia lattice, preventing the evolution of the undesirable monoclinic‐ZrO2 phase.